Microwave-assisted preparation method of nickel-doped copper sulfide material for lithium / sodium ion battery negative electrode and application thereof
Patent Information
- Application Number
- CN202610924513.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]本发明针对现有镍掺杂硫化铜制备方法中存在的反应周期长、能耗高、需高压密闭体系导致安全隐患大、掺杂均匀性难以精确控制等问题,提供一种锂/钠离子电池负极用镍掺杂硫化铜材料的微波辅助制备方法及其应用
1. 本发明首次将常压微波辅助合成技术应用于镍掺杂硫化铜(Ni-CuS)负极材料的制备,突破了传统水热/溶剂热法需要密闭高压、长时间加热(数小时至数十小时)的技术局限,将反应时间大幅缩短至150秒,实现了常压条件下金属硫化物成核、结晶与镍元素均匀掺杂的一步完成,合成效率显著提升。
Smart Images

Figure CN122877796A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage materials technology, specifically relating to a microwave-assisted preparation method for nickel-doped copper sulfide material for lithium / sodium-ion battery anodes and its application. Background Technology
[0002] With the global energy structure transformation and the advancement of "dual-carbon" goals, electrochemical energy storage technology has become crucial for supporting the large-scale utilization of renewable energy. Lithium-ion batteries, with their high energy density and long cycle life, are widely used in portable electronic devices and electric vehicles. However, the limited reserves and uneven geographical distribution of lithium resources lead to continuous cost fluctuations, making it difficult to meet the dual demands of economic efficiency and sustainability for large-scale stationary energy storage. Against this backdrop, sodium-ion batteries, due to their abundant sodium resources, low cost, and similar "rocking chair" operating principle to lithium-ion batteries, are considered an ideal candidate technology for large-scale energy storage systems. Whether lithium-ion batteries pursue higher energy density or sodium-ion batteries strive for low-cost, long-life energy storage, high-performance anode materials are key components determining the overall battery performance.
[0003] Among numerous anode material systems, transition metal sulfides have become a research hotspot in the field of lithium-ion and sodium-ion battery anode materials due to their theoretical specific capacity, which is far higher than that of traditional carbon materials, and their unique physicochemical properties. Copper sulfide (CuS), in particular, has a layered crystal structure, with its layers connected by relatively weak van der Waals forces and a large interlayer spacing, which is conducive to the formation of larger alkali metal ions (Li₂O₃). + and Na + Rapid insertion and extraction of CuS. Simultaneously, CuS can undergo multiple redox reactions during electrochemical reactions, involving Cu... 2+ / Cu + / Cu 0 The conversion of sulfides and polysulfides contributes to the high theoretical specific capacity. However, CuS faces two common challenges in practical applications as an anode material: firstly, its poor intrinsic electronic conductivity limits the rate performance of the electrode; secondly, the significant volume effect during repeated charge-discharge cycles leads to the pulverization of the active material, loss of electrical contact with the current collector, and repeated rupture and regeneration of the solid electrolyte interphase (SEI) film, ultimately resulting in rapid decay of reversible capacity and shortened cycle life [Journal of Materials Chemistry A, 2019, 7: 21903]. These problems are particularly prominent in sodium-ion batteries because Na... + The ionic radius of Cu⁺ (1.02 Å) is significantly larger than that of Li⁺ (0.76 Å), and its insertion / extraction in the CuS lattice will induce more intense volume expansion and slower solid-state diffusion dynamics.
[0004] Elemental doping is an effective means of controlling the electronic structure and crystal stability of transition metal sulfides. Studies have shown that introducing heterovalent transition metal ions (such as nickel ions, Ni) into the CuS lattice is effective. 2+ Nickel-doped copper sulfide (Ni-CuS) can form impurity energy levels in the band structure, increasing carrier concentration and thus enhancing the intrinsic electronic conductivity of the material. Simultaneously, the strong chemical bonding between the dopant ions and the sulfur framework can create a "pinning" effect on the crystal structure, effectively suppressing lattice expansion and structural collapse during the insertion / extraction of alkali metal ions, thereby improving the material's cycle stability. Therefore, Ni-doped copper sulfide (Ni-CuS) is considered a promising bifunctional anode material suitable for both lithium-ion and sodium-ion batteries.
[0005] However, almost all reported methods for preparing nickel-doped copper sulfide materials currently rely on traditional hydrothermal or solvothermal methods. These methods typically require long-term reactions lasting several hours or even tens of hours in a closed, high-pressure reactor at high temperatures. This not only results in lengthy process cycles and enormous energy consumption, but also poses safety risks due to the closed, high-pressure system, poor batch-to-batch reproducibility, and difficulty in achieving large-scale industrial production. More importantly, the traditional long-term heating process easily leads to uneven distribution of dopant elements, making it difficult to precisely control the doping amount, product morphology, and crystal structure. Therefore, there is an urgent need to develop a new method for preparing nickel-doped copper sulfide that is rapid, efficient, safe, and easily scalable to simultaneously improve the material's lithium and sodium storage electrochemical performance, promoting its practical application in lithium-ion and sodium-ion batteries. Summary of the Invention
[0006] This invention addresses the problems of long reaction cycles, high energy consumption, safety hazards due to the need for high-pressure closed systems, and difficulty in precisely controlling doping uniformity in existing nickel-doped copper sulfide preparation methods. It provides a microwave-assisted preparation method for nickel-doped copper sulfide materials for lithium / sodium-ion battery anodes and its applications. This invention utilizes the rapid bulk heating and molecular polarization perturbation effect of microwave irradiation to achieve nucleation, crystallization, and uniform nickel doping of metal sulfides in a single step under ambient pressure and in a very short time, thereby simultaneously improving the electrochemical performance and large-scale production efficiency of the material.
[0007] The present invention adopts the following technical solution: A microwave-assisted preparation method for nickel-doped copper sulfide materials used as anodes in lithium / sodium-ion batteries is disclosed. The method employs a microwave-assisted synthesis strategy, using nickel and copper salts dissolved in ethylene glycol as metal sources and thiourea dissolved in ethylene glycol as a sulfur source. The nickel-doped copper sulfide material is prepared in one step via a rapid microwave irradiation reaction. The method includes the following steps: A microwave-assisted preparation method for nickel-doped copper sulfide material used as a negative electrode in lithium / sodium-ion batteries includes the following steps: S1. Dissolve nickel nitrate hexahydrate and copper nitrate trihydrate in ethylene glycol to obtain solution A; dissolve thiourea in ethylene glycol to obtain solution B; S2. At room temperature, stir solutions A and B separately, then mix solutions A and B together and continue stirring to obtain a mixed solution; S3. Place the mixed solution obtained in S2 in a microwave reactor under normal pressure and react at 400 W power for 150 s to obtain a black precipitate; S4. After the black precipitate cools to room temperature, wash it several times with ethylene glycol, and then dry it under vacuum to obtain the nickel-doped copper sulfide anode material, denoted as Ni-CuS.
[0008] Furthermore, in S1, the amounts of nickel nitrate hexahydrate and copper nitrate trihydrate are 1:1 in terms of the atomic ratio of Ni to Cu; and the amount of thiourea is in excess.
[0009] Further, in S1, the amount of nickel nitrate hexahydrate is 1.1 g, the amount of copper nitrate trihydrate is 0.9 g, each dissolved in 15 ml of ethylene glycol; the amount of thiourea is 1.14 g, dissolved in 15 ml of ethylene glycol.
[0010] Furthermore, in S2, the stirring rate of both solution A and solution B is 500 r / min, and the stirring time is 30 min; after mixing, the stirring rate continues to be 500 r / min, and the stirring time is 10 min.
[0011] Furthermore, in S4, the vacuum drying temperature is 80°C and the drying time is 12 hours.
[0012] Another objective of this invention is to provide a nickel-doped copper sulfide anode material.
[0013] Another objective of this invention is to provide an application of nickel-doped copper sulfide anode material in lithium / sodium-ion battery anodes.
[0014] The beneficial effects of this invention are as follows: 1. This invention is the first to apply atmospheric pressure microwave-assisted synthesis technology to the preparation of nickel-doped copper sulfide (Ni-CuS) anode materials, breaking through the technical limitations of traditional hydrothermal / solvothermal methods that require closed high pressure and long heating time (several hours to tens of hours). The reaction time is greatly shortened to 150 seconds, realizing the one-step completion of metal sulfide nucleation, crystallization and uniform nickel doping under atmospheric pressure, and the synthesis efficiency is significantly improved.
[0015] 2. This invention utilizes the unique bulk heating and molecular polarization perturbation effect of microwave irradiation to drive the reaction system to uniformly heat up in a very short time, effectively avoiding the problem of uneven doping caused by temperature gradients in traditional heating methods, ensuring the uniform distribution of nickel ions in the copper sulfide lattice, thereby achieving precise control over the electronic structure and crystal stability of the product.
[0016] 3. This invention uses ethylene glycol as a solvent and microwave absorption medium, and achieves simultaneous morphology control of the product through microwave-assisted synthesis. It can obtain nanostructured nickel-doped copper sulfide materials without the need for additional template agents or surfactants. The process is green and simple, and subsequent purification is easy.
[0017] 4. This invention can achieve systematic adjustment of product doping amount and electrochemical performance by simply controlling the atomic ratio of nickel to copper. This method has good composition scalability and provides a universal and efficient new approach for the doping modification of transition metal sulfide anode materials. Attached Figure Description
[0018] Figure 1 The images show scanning electron microscope (SEM) images of synthesized CuS, Ni-CuS, and 2Ni-CuS. In the figures: a and b represent CuS; c and d represent Ni-CuS; e and f represent 2Ni-CuS. Figure 2 X-ray diffraction patterns of CuS, Ni-CuS, and 2Ni-CuS; Figure 3 The images show transmission electron microscope (TEM) images of the synthesized Ni-CuS; in the images: a is a TEM image at the 100 nm scale; b is a TEM image at the 20 nm scale; c is a TEM image at the 5 nm scale. Figure 4 The image shows the elemental distribution of the synthesized Ni-CuS; in the image: a is a scanning electron microscope image at the 1 μm scale; b is the elemental distribution of C; c is the elemental distribution of N; d is the elemental distribution of O; e is the elemental distribution of Ni; f is the elemental distribution of Cu; g is the elemental distribution of S. Figure 5 The figures show the X-ray photoelectron spectra of CuS, Ni-CuS, and 2Ni-CuS. In the figures: a is the full spectrum; b is a magnified Cu 2p spectrum; c is a magnified S 2p spectrum. Figure 6 The figures show the electrochemical performance test curves for CuS, Ni-CuS, and 2Ni-CuS. In the figure: a is the rate performance curve at different current densities; b is the cycling curve at a current density of 0.1 A / g; c is the cycling curve at a current density of 5 A / g. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains, and all materials publicly cited herein and cited by them are incorporated herein by reference.
[0021] Equivalent technologies of the specific embodiments described herein that are apparent to those skilled in the art through routine experimentation are included in this application.
[0022] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the instruments and equipment used in the following examples are all standard laboratory instruments and equipment; unless otherwise specified, the experimental materials used in the following examples were all purchased from regular biochemical reagent stores.
[0023] Example 1 Preparation of copper sulfide (CuS) comparative samples: raw materials: copper nitrate trihydrate (Cu(NO3)2·3H2O), thiourea (CH4N2S), ethylene glycol.
[0024] Procedure: Weigh 0.9 g of copper nitrate trihydrate and dissolve it in 15 mL of ethylene glycol to obtain solution A; weigh 1.14 g of thiourea and dissolve it in 15 mL of ethylene glycol to obtain solution B. Stir solutions A and B separately at 500 r / min for 30 min at room temperature. Then pour solution A into solution B and continue stirring at 500 r / min for 10 min to obtain a mixed solution. Place the mixed solution in a microwave reactor at atmospheric pressure and react at 400 W for 150 s to obtain a black precipitate. After it cools naturally to room temperature, wash it several times with ethylene glycol and dry it in a vacuum drying oven at 80 ℃ for 12 h to obtain the copper sulfide control sample CuS.
[0025] Example 2 Preparation of nickel-doped copper sulfide (Ni-CuS): Raw materials: nickel nitrate hexahydrate (Ni(NO3)2·6H2O), copper nitrate trihydrate (Cu(NO3)2·3H2O), thiourea (CH4N2S), ethylene glycol.
[0026] Procedure: Weigh 1.1 g of nickel nitrate hexahydrate and 0.9 g of copper nitrate trihydrate and dissolve them simultaneously in 15 mL of ethylene glycol to obtain solution A; weigh 1.14 g of thiourea and dissolve it in 15 mL of ethylene glycol to obtain solution B. Stir solutions A and B separately at 500 r / min for 30 min at room temperature. Then pour solution A into solution B and continue stirring and mixing at 500 r / min for 10 min to obtain a homogeneous mixed solution. Place the mixed solution in a microwave reactor at atmospheric pressure and react at 400 W power for 150 s to obtain a black precipitate. After it cools naturally to room temperature, wash it several times with ethylene glycol and dry it in a vacuum drying oven at 80 ℃ for 12 h to obtain the nickel-doped copper sulfide product Ni-CuS. In this example, the atomic ratio of Ni to Cu is 1:1.
[0027] Example 3 Preparation of high-nickel-doped copper sulfide (2Ni-CuS) comparative sample: raw materials: nickel nitrate hexahydrate (Ni(NO3)2·6H2O), copper nitrate trihydrate (Cu(NO3)2·3H2O), thiourea (CH4N2S), ethylene glycol.
[0028] Procedure: Weigh 2.2 g of nickel nitrate hexahydrate and 0.9 g of copper nitrate trihydrate and dissolve them simultaneously in 15 mL of ethylene glycol to obtain solution A; weigh 1.14 g of thiourea and dissolve it in 15 mL of ethylene glycol to obtain solution B. Stir solutions A and B separately at 500 r / min for 30 min at room temperature. Then pour solution A into solution B and continue stirring at 500 r / min for 10 min to obtain a mixed solution. Place the mixed solution in a microwave reactor at atmospheric pressure and react at 400 W power for 150 s to obtain a black precipitate. After it cools naturally to room temperature, wash it several times with ethylene glycol and dry it in a vacuum drying oven at 80 ℃ for 12 h to obtain the high-nickel-doped copper sulfide comparative sample 2Ni-CuS. In this example, the atomic ratio of Ni to Cu is 2:1.
[0029] As attached Figure 1Scanning electron microscopy revealed significantly different microstructures in the three samples. The CuS comparative sample from Example 1 exhibited a typical layered assembly structure, with disordered stacking of nanosheets, a relatively smooth surface, and obvious gaps between the layers. The Ni-CuS product from Example 2 exhibited a regular octahedral assembly morphology, composed of ordered stacking of fine nanoparticles, with a rough surface and densely packed granular secondary structures. While the Ni-CuS comparative sample from Example 3 also exhibited an octahedral assembly morphology, its surface tended to be smoother, the boundaries between assembly units were blurred, and the granular secondary structures essentially disappeared. This indicates that excessive nickel doping altered the surface energy and growth kinetics of the crystal, causing the assembly surface to become smoother. The above morphological evolution suggests that appropriate nickel doping (Ni:Cu = 1:1) can induce copper sulfide to transform from disordered layered assembly to regular octahedral assembly, while simultaneously endowing the assembly surface with abundant nanoparticle-like rough structures. Excessive nickel doping, on the other hand, makes the assembly surface smoother, which is detrimental to the exposure of active sites.
[0030] As attached Figure 2 As shown in the X-ray diffraction pattern, all diffraction peaks of the CuS comparative sample obtained in Example 1 are completely consistent with the standard card (PDF#06-0464) of hexagonal copper sulfide. Characteristic diffraction peaks were observed at 2θ of 27.7°, 29.3°, 31.8°, 32.9°, 47.9°, 52.7°, and 59.3°, corresponding to the (101), (102), (103), (006), (110), (108), and (116) crystal planes, respectively, indicating that pure hexagonal CuS was synthesized. The diffraction peak positions of the Ni-CuS sample obtained in Example 2 are completely consistent with those of CuS in Example 1, and no new diffraction peaks or impurity phase peaks appear. This result indicates that nickel ions successfully enter the CuS lattice and occupy copper ion sites through isomorphous substitution, without forming independent nickel sulfide or nickel oxide impurity phases. Nickel doping did not change the main phase crystal structure of copper sulfide. The diffraction pattern of the 2Ni-CuS comparative sample obtained in Example 3 shows the superposition of characteristic diffraction peaks of hexagonal CuS (PDF#06-0464) and cubic CuS2, indicating that excessive nickel doping has exceeded the solid solution limit of the copper sulfide lattice, inducing some copper ions to transform into the CuS2 phase with higher sulfur coordination valence states, resulting in obvious phase separation. The above XRD analysis confirms that controlling the Ni:Cu atomic ratio to 1:1 can achieve complete solid solution doping of nickel in the copper sulfide lattice, maintaining a single pure phase structure, which is beneficial to fully utilizing the optimization effect of nickel doping on electronic structure and cycle stability.
[0031] As attached Figure 3Transmission electron microscopy (TEM) revealed a distinct carbon layer encapsulation structure on the surface of the Ni-CuS particles obtained in Example 2. The carbon layer was uniform in thickness and tightly bonded to the particle core. This carbon layer originated from the partial carbonization of thiourea during the microwave reaction, which is beneficial for improving the electronic conductivity of the material and buffering volume changes during charge and discharge. High-resolution TEM images showed clear lattice fringes, indicating good crystallinity of the obtained material. The measured interplanar spacing was consistent with the crystal parameters of hexagonal copper sulfide. Furthermore, the localized lattice distortion caused by nickel doping further confirmed the successful entry of nickel ions into the CuS lattice.
[0032] As attached Figure 4 As shown in the elemental distribution diagram, C, N, O, Ni, Cu, and S exhibit uniform distribution at the particle scale, with no obvious elemental agglomeration or phase separation. The uniform distribution of C and N confirms the complete carbon layer coating and the in-situ introduction of nitrogen-containing functional groups. The synchronous and uniform distribution of Ni with Cu and S strongly demonstrates that the microwave-assisted synthesis strategy achieves highly uniform doping of nickel ions in the copper sulfide lattice, effectively avoiding the local enrichment problem of dopant elements that may occur with traditional long-term heating methods.
[0033] As attached Figure 5 The full X-ray photoelectron spectroscopy (XPS) spectrum of sample a shows that five elements—Cu, O, N, C, and S—were detected on the surface of the CuS sample obtained in Example 1. In addition to the five elements mentioned above, the full spectra of the Ni-CuS sample obtained in Example 2 and the 2Ni-CuS sample obtained in Example 3 also showed characteristic signals of Ni element, directly confirming the successful incorporation of nickel into the product. (See attached image.) Figure 5 The high-resolution Cu2p spectra of b are shown, illustrating the Cu2p spectra of the three samples. 3 / 2 and Cu 2p 1 / 2 The characteristic peak positions were basically consistent, and the peak shape and binding energy did not show significant shifts, indicating that nickel doping did not significantly alter the chemical valence state and coordination environment of copper ions. (See attached image) Figure 5 As shown in the high-resolution S 2p spectrum of c, CuS in Example 1 exhibits S 2p at low binding energies. 3 / 2 and S 2p 1 / 2 The spin-orbit splitting peak is attributed to S in metal sulfides. 2-Species. Compared to CuS, the S 2p characteristic peaks of Ni-CuS in Example 2 and 2Ni-CuS in Example 3 are significantly shifted towards higher binding energies. This chemical shift indicates that the introduction of nickel ions alters the electron cloud density around sulfur atoms. Since nickel has a higher electronegativity (1.91) than copper (1.90), the formation of Ni-S bonds reduces the electron cloud density around sulfur atoms, leading to an increase in the S 2p binding energy. The XPS analysis results and XRD characterization conclusions corroborate each other, jointly confirming that the microwave-assisted synthesis strategy successfully achieved uniform solid solution doping of nickel ions in the copper sulfide lattice.
[0034] As attached Figure 6 As shown in the rate performance diagram, the Ni-CuS obtained in Example 2 exhibits the best rate performance at progressive current densities from 0.1 A / g to 5 A / g. Its reversible specific capacity hardly decreases as the current density gradually increases from 0.1 A / g to 5 A / g, maintaining a capacity retention rate of over 99%, demonstrating excellent fast charge-discharge capability. The 2Ni-CuS obtained in Example 3 shows the second best rate performance, but its capacity decreases to some extent at high current densities. The CuS obtained in Example 1 shows the worst rate performance compared to the control sample, with significant capacity decay as the current density increases. These results indicate that appropriate nickel doping (Ni:Cu = 1:1) can significantly improve the electronic conductivity and sodium ion migration kinetics of copper sulfide materials, thereby endowing the materials with excellent rate performance. (See attached diagram) Figure 6 As shown in the long-cycle performance graph (b), at a current density of 0.1 A / g, the CuS of Example 1 and the 2Ni-CuS of Example 3 exhibited high initial reversible specific capacity in the first 20 cycles, but subsequently both showed significant capacity decay, ultimately maintaining only 100-150 mAh / g after 100 cycles. This indicates that the undoped or excessively nickel-doped materials underwent severe structural damage and loss of active material during repeated charge-discharge cycles. In contrast, the Ni-CuS obtained in Example 2 maintained a stable reversible specific capacity of around 500 mAh / g after 100 cycles at a current density of 0.1 A / g, demonstrating excellent capacity retention. (See attached graph) Figure 6 As shown in the long-cycle performance graph, under a high current density of 5 A / g, the Ni-CuS electrode exhibits excellent long-cycle stability, with its capacity remaining stable at around 300 mAh / g after 1000 cycles. This electrochemical performance comparison clearly demonstrates that uniform solid solution doping achieved by controlling the Ni:Cu atomic ratio to 1:1 effectively suppresses volume expansion and structural pulverization during charge and discharge, ensuring both high specific capacity and excellent long-cycle stability. In contrast, the undoped sample suffers from continuous capacity decay due to poor conductivity and structural instability, while excessive nickel doping accelerates electrode material failure due to the presence of impurity phases.
[0035] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A microwave-assisted preparation method for nickel-doped copper sulfide material for lithium / sodium-ion battery anodes, characterized in that: A microwave-assisted synthesis strategy was adopted, in which nickel salts and copper salts were dissolved in ethylene glycol as metal sources, and thiourea was dissolved in ethylene glycol as sulfur source. The nickel-doped copper sulfide material was prepared in one step by rapid reaction through microwave irradiation.
2. The microwave-assisted preparation method for nickel-doped copper sulfide material for lithium / sodium-ion battery anodes according to claim 1, characterized in that: Includes the following steps: S1. Dissolve nickel nitrate hexahydrate and copper nitrate trihydrate in ethylene glycol to obtain solution A; dissolve thiourea in ethylene glycol to obtain solution B; S2. At room temperature, stir solutions A and B separately, then mix solutions A and B together and continue stirring to obtain a mixed solution; S3. Place the mixed solution obtained in S2 in a microwave reactor under normal pressure and react at 400 W power for 150 s to obtain a black precipitate; S4. After the black precipitate cools to room temperature, wash it several times with ethylene glycol, and then dry it under vacuum to obtain the nickel-doped copper sulfide anode material, denoted as Ni-CuS.
3. The microwave-assisted preparation method for nickel-doped copper sulfide material for lithium / sodium-ion battery anodes according to claim 2, characterized in that: In S1, the amounts of nickel nitrate hexahydrate and copper nitrate trihydrate are 1:1 in terms of the atomic ratio of Ni to Cu; the amount of thiourea is in excess.
4. The microwave-assisted preparation method for nickel-doped copper sulfide material for lithium / sodium-ion battery anodes according to claim 3, characterized in that: In S1, the amount of nickel nitrate hexahydrate is 1.1 g, the amount of copper nitrate trihydrate is 0.9 g, each dissolved in 15 ml of ethylene glycol; the amount of thiourea is 1.14 g, dissolved in 15 ml of ethylene glycol.
5. The microwave-assisted preparation method for nickel-doped copper sulfide material for lithium / sodium-ion battery anodes according to claim 2, characterized in that: In S2, the stirring rate of both solution A and solution B is 500 r / min, and the stirring time is 30 min; after mixing, the stirring rate continues at 500 r / min, and the stirring time is 10 min.
6. The microwave-assisted preparation method for nickel-doped copper sulfide material for lithium / sodium-ion battery anodes according to claim 2, characterized in that: In S4, the vacuum drying temperature is 80°C and the drying time is 12 hours.
7. A nickel-doped copper sulfide anode material prepared by the preparation method according to any one of claims 1-6.
8. The application of the nickel-doped copper sulfide anode material as described in claim 7 in the anode of a lithium / sodium-ion battery.